Associations between Volunteering and Mental Health during COVID-19 among Chinese Older Adults. Issue 6 (18th August 2021) - Chan, Wai; Chui, Cheryl Hiu Kwan; Cheung, Johnson Chun Sing; Lum, Terry Yat Sang; Lu, Shiyu
ABSTRACT: Evidence about the association between volunteering and the mental health of older adults during COVID-19 remains underexplored. This study investigated (1) patterns of volunteering among older adults in Hong Kong during COVID-19; (2) associations between volunteering and mental health of older adults during COVID-19; and (3) associations between key psychological resources (e.g., self-efficacy and self-esteem) and volunteering among older adults during COVID-19. This study applied a cross-sectional design with data collected from 128 older adults in June 2020, who were trained as volunteers in a volunteer program that began before COVID-19. The study found that older adults continued to actively contribute to their communities by engaging in volunteering during COVID-19. The specific type of volunteering activities was linked to few depressive and anxiety symptoms. Older adults with increased self-esteem prior to COVID-19 were more likely to participate in volunteering activities related to COVID-19. Our study suggested that encouraging older adults to volunteer during the pandemic is a key pathway to maintain mental health. Social workers are encouraged to engage older adults in volunteerism regularly to offset the risk of depression and anxiety symptoms in times of crisis.